Proprioception is not associated with lower extremity injuries in U21 high-level football players - Namazi, P.; Zarei, M.; Abbasi, H.; Hovanloo, F.; Rommers, N.; Rössler, R. (European Journal of Sport Science, 2020)
Football is a contact sport with a significant risk of injury. Although proprioception is well studied in rehabilitation, little is known about the association between proprioception and the occurrence of sport injuries. The purpose of this study was to look into the association between ankle and knee proprioception and lower extremity injuries in young football players. Seventy-three football players from the highest U-21 league in Iran volunteered to participate in this study. Before the start of the 2017-2018 competitive season, joint position sense was measured at 30°, 60° and 90° knee flexion and at 10° and 15° ankle dorsiflexion, and inversion using the Biodex Isokinetic pro 4 system. The teams` medical staff recorded football-related lower extremity injuries. We used mixed effects Cox regression models to calculate hazard ratios (HRs) with 95% CIs, acknowledging the clustered data structure. Twenty-two players (30.1%) suffered one or more lower extremity injuries during the season. None of the proprioception measures examined was significantly associated with the risk of lower extremity injuries. Based on these results of our sample, joint position sense does not seem to be associated with lower extremity injuries in young male football players.